2018
DOI: 10.1159/000489111
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-34a Inhibition of the TLR Signaling Pathway Via CXCL10 Suppresses Breast Cancer Cell Invasion and Migration

Abstract: Background/Aims: Breast cancer (BC) starts as a local disease, but it can metastasize to the lymph nodes and distant organs. However, the metastatic process is still poorly understood. The mRNA microarray datasets GSE26910 and GSE33447 show that CXCL10 is up-regulated in BC, and the microRNA microarray dataset GSE38167 and a network meta-analysis of microRNA expression profile studies in human BC suggest that microRNA-34a (miR-34a) is down-regulated in BC. CXCL10 was predicted as a target of miR-34a by microRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 47 publications
(51 reference statements)
1
17
0
1
Order By: Relevance
“…In their study, the miR-34a molecule was found to inhibit C-X-C motif ligand 10 (CXCL10). The ligand is characterized by a strong affinity to TLR, promoting cancerogenic downsignaling [97,98]. Indirect inhibition of TLR signaling results in the regression of tumor growth and expansion.…”
Section: Mirna/tlr-4 Interplaymentioning
confidence: 99%
“…In their study, the miR-34a molecule was found to inhibit C-X-C motif ligand 10 (CXCL10). The ligand is characterized by a strong affinity to TLR, promoting cancerogenic downsignaling [97,98]. Indirect inhibition of TLR signaling results in the regression of tumor growth and expansion.…”
Section: Mirna/tlr-4 Interplaymentioning
confidence: 99%
“…In this work, for example, we show that apigenin suppressed the TNFα mediated rise in a potent tumor suppressor: CXCL10. While previous studies consistently that CXCL10 is up-regulated in normal vs. tumor tissue (76,77) this particular protein acts as the major tumor suppressor, evoked by IFN-γ treatment and somehow plays a role in the re-expression of MHC-1, PD-L1, the infiltration of anti-tumoral CD4(+) and CD8(+) T cells (78,79), NK cells, cytotoxic lymphocytes (CTLs) to the tumor to turn on immune surveillance and heighted survival odds in diverse human cancers (80)(81)(82). While the beneficial effects of apigenin in cancer are consistently reported, any compound that would turn off the CXCL9, -10, -11/CXCR3 axis could harm the host immunes system to destroy self-malignant tumor tissue (83).…”
Section: Discussionmentioning
confidence: 76%
“…In recent years, great progress has been made in the investigation of miR-34a in breast cancer ( 19 21 ). Previous studies have demonstrated that multiple miRNAs are abnormally expressed in breast cancer and are closely associated with the development of this tumor ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%